Self-Regulation Learning Sebagai Solusi Mahasiswa yang Sudah Menikah dalam Menyelesaikan Tugas Akhir di UIN Palangka Raya - Junita Wulandari; M. Ali Sibram Malisi; Surawan Surawan (Kamaya: Jurnal Ilmu Agama, 2025)
Married students often face dual roles that hinder the effectiveness of completing their final assignments, making Self-Regulated Learning (SRL) an essential skill for maintaining academic performance. This study aims to analyze how SRL is implemented by final-semester married students at UIN Palangka Raya in completing their thesis work. A qualitative case study design was employed, involving ten participants selected through in-depth interviews, observations, and documentation. The findings reveal that 8 out of 10 participants experienced significant time constraints due to household and work responsibilities, while 6 participants reported stress caused by repeated thesis revisions. Field data show diverse SRL strategies: Hanida could only work on her thesis between Zuhr and Asr after leaving her child with family; Nania woke up at 04:00 to manage household duties before work; Aulia completed thesis tasks during quiet hours at his shop; and Jannah temporarily stopped writing due to baby blues before resuming her thesis with parental support. Additional barriers included financial difficulties such as losing a laptop, learning loafing, and academic burnout that led students to seek new study environments such as cafés. The study concludes that SRL functions as an adaptive mechanism enabling married students to balance academic demands and family responsibilities, and their success is strongly influenced by structured planning, disciplined time management, stable motivation, and consistent social support from spouses, parents, and peers.